Improving Compliance with the Use of Ankle Foot Orthosis in Children with Cerebral Palsy through a Family-Based Health Promotion Model: Systematic Literature Review - M Syafii; Suryo Ediyono (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
This study aims to systematically synthesize the characteristics, components, theoretical framework, determinants, barriers, effectiveness, and research gaps related to family-based health promotion models in improving compliance with the use of ankle foot orthosis (AFO) in children with cerebral palsy (CP). The method used is Systematic Literature Review (SLR) with the PRISMA 2020 approach through a search of the Scopus database using keywords related to Family Health Promotion, Orthosis Use Adherence, and Pediatric Cerebral Palsy. Of the 659 initial articles, 71 main studies and 2 additional sources met the inclusion criteria to be analyzed through thematic synthesis and narrative integrative review. The results show that there is no single model that specifically integrates family-based health promotion to improve adherence to the use of AFO in CP children, but the literature provides a strong foundation through Family Systems Theory, Pender's Health Promotion Model, WHO Adherence Model, caregiver empowerment, personalized orthotic care, and digital health support. Key factors influencing compliance include family support, caregiver burden, self-efficacy, device comfort, health system, and social environment. In conclusion, improving compliance with the use of AFO requires an integrative approach that places the family at the center of health promotion, as well as opening up opportunities for the development of new conceptual models that are more comprehensive, personalized, and sustainable.